cfDNA Changes in Maximal Exercises as a Sport Adaptation Predictor - Humińska-Lisowska, Kinga; Mieszkowski, Jan; Kochanowicz, Andrzej; Stankiewicz, Błażej; Niespodziński, Bartłomiej; Brzezińska, Paulina; Ficek, Krzysztof; Kemerytė-Ivanauskienė, Eglė; Cięszczyk, Paweł (Genes, 2021)
Changes of circulating free plasma DNA (cfDNA) are associated with different types of tissue injury, including those induced by intensive aerobic and anaerobic exercises. Observed changes are dependent from induced inflammation, and thus it may be a potential marker for athletic overtraining. We aimed to identify the response of cfDNA to different types of exercise, with association to exercise intensity as a potential marker of exercise load. Fifty volunteers (25 athletes and 25 physically active men) were assigned to the study and performed maximal aerobic (Bruce test) and anaerobic (Wingate Anaerobic Test) test. Blood samples for cfDNA analysis were collected at four time-points: before, 2-5 min after, 30 min after and 60 min after each type of maximal physical activity. The two-way ANOVA revealed a significant effect of group factor on serum cfDNA concentrations (32.15% higher concentration of cfDNA in the athletes). In turn the results of the post hoc test for the interaction of the repeated measures factor and the group showed that while the concentration of cfDNA decreased by 40.10% in the period from 30 min to 60 min after exercise in the control group, the concentration of cfDNA in the group of athletes remained at a similar level. Our analysis presents different responses depending on the intensity and duration of exercise. Our observations imply that formation of cfDNA is associated with response to physical activity but only during maximal effort.
Keywords: fyziologická adaptace; anaerobic exercise; mužské pohlaví; exercise load; studie případů a kontrol; mladý dospělý; aerobic exercise; cfDNA; sporty; Young Adult; Humans; biologické markery; Cell-Free Nucleic Acids; volné cirkulující nukleové kyseliny; Case-Control Studies; Biomarkers; Sports; lidé; Male; Adaptation, Physiological